VD_FINDINFO Arrêt / 2016 / 290 vom 22. Juli 2016 - VD Tribunal cantonal (2016)
DEGRÉ DE L'INCAPACITÉ DE TRAVAIL, REVENU D'INVALIDE | 28 al. 1 LAI, 28 al. 2 LAI, 28a al. 1 LAI, 4 al. 1 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA